Fostering of social, emotional, and cognitive skills in elementary schools: the Papilio-6to9 program - Lechner, Viola; Ortelbach, Niklas; Scheithauer, Herbert (Frontiers in Psychology, 2025)
BackgroundInternational guidelines emphasize the importance of holistic personal development in education, incorporating both academic and social–emotional skills. The developmentally appropriate, school-based prevention program Papilio-6to9 for students aged six to nine, implemented by trained teachers, aims at improving social, emotional, and cognitive skills and preventing behavior and emotional problems. The program differs from existing school-based prevention programs in Germany in its theoretical framework and multi-level approach targeting both students and teachers. The current study is the first to assess program effectiveness by analyzing the impact on the student-level outcomes.MethodsThe pilot study employed a randomized waiting control group longitudinal design with three measurement points (pre-test, post-test, follow-up). The sample comprised 224 children (52% girls, age M = 7.1 years) from twelve classes. Teachers completed online questionnaires at each measurement point, assessing social–emotional problems, social skills, executive functions, and student-teacher relationship.ResultsThe results indicated program effects in all defined outcome areas: program participation was associated with lower problem scores, higher social skills, higher executive functions, and closer student-teacher relationship.ConclusionThe findings of the pilot evaluation indicate the effectiveness of the Papilio-6to9 program in promoting social–emotional skills and preventing emotional and behavioral problems. Future studies should aim to validate the findings with a larger sample and incorporate multiple sources of information. Limitations and recommendations for future research are discussed.